CONTEMPORARY CHALLENGES THAT HINDER BUILDING KNOWLEDGE SOCIETY IN JORDAN FROM THE EDUCATIONAL EXPERTS PERSPECTIVE - Al-Slaihat, Malouh Mfadi (European Scientific Journal, ESJ, 2013)
This study aimed at revealing the contemporary challenges that hinder building knowledge society in Jordan from the perspective of the educational experts , through answering the following two questions: 1. What are the contemporary challenges that hinder building knowledge society in Jordan from the prospective of the educational experts? 2. Are the contemporary challenges which hinder building knowledge society differ according to the difference of the place of work, job, scientific qualification and educational expertise? To achieve the objective of the study, a questionnaire, the tool of the study, was developed and it consisted of 30 items representing the challenges that prevent building knowledge society in different fields. After achieving the tool’s reliability and validity, it was applied on a sample of a study consisted of (235) educational expert. The results of the study revealed that the experts’ evaluation of these challenges was high. the results also ensured that there were significant differences in the challenges that hinder building society of knowledge regarding the variables; place of work and educational expertise at the level of significance (a=0.05) and the differences were respectively in favor of Al-Hussein Bin Talal University and in favor of whose experiences is less than five years. And there were no significant effect to the job and the scientific qualification variables. Based on these results, the study recommended the necessity of having strategic changes in the academic education’s system in Jordan which are compatible with the requirements of building knowledge society .